PERATURAN RESTORATIVE JUSTICE DALAM PERATURAN MAHKAMAH AGUNG NO. 1 TAHUN 2024 - Pradana, Aditya Anaris; Santoso, Bambang (Sebelas Maret University, 2025)
Supreme Court (PERMA) Regulation No. 1 of 2024 on Restorative Justice integrates the principles of restorative justice into the Indonesian criminal justice system, with the aim of creating a more just, humane, and sustainable solution in the handling of criminal offences. Restorative justice emphasizes the recovery of victims' losses, the accountability of perpetrators, and the restoration of social ties disrupted by crime. This article discusses the basic principles of restorative justice, the procedures of filing and enforcement, the benefits offered, as well as the challenges faced in its implementation. With adequate training, effective socialization, and infrastructure development, restorative justice is expected to make a positive contribution to the criminal justice system in Indonesia.